The Effect Of E-WOM And Source Credibility Of Instagram Account @racunshopeecheck On Customer Path 5A (Aware, Appeal, Ask, Act, Advocate) - Tharisa Azzahra Rizky; Indria Angga Dianita (Business Journal : Jurnal Bisnis Dan Sosial, 2022)
One of the marketplaces that has managed to get a lot of users in Indonesia is Shopee. Having many users encourages Shopee to develop features that can facilitate and satisfy its users. One new feature launched by Shopee is Shopee Affiliate Program. Among many affiliates account in Instagram, @racunshopeecheck Instagram account has the highest followers’ and engagement rate. To maintain audiences and compete with other competitors, @racunshopeecheck as an affiliate needs to create an innovative marketing strategy to attract and moved audiences to act. Therefore, this study aims to analyze the effect of E-WOM and source credibility on customer path 5A. Through this research, it is hoped that it can produce an appropriate marketing strategy that can run customer path 5A effectively. This research was conducted using quantitative methods with descriptive research type. The sampling technique used in this study is probability sampling, with simple random sampling techniques. The analysis technique uses a normality test, multicollinearity test, heteroscedasticity test, coefficient correlation test, coefficient of determination, and multiple linear regression. Based on the study results, E-WOM partially influenced Customer Path 5A by 81,6%, and the remaining 18,4% was influenced by other factors not examined in this study. Source Credibility partially influenced Customer Path 5A by 84,2%, and the remaining 15,8% was influenced by other factors not examined in this study. E-WOM and Source Credibility simultaneously influenced Customer Path 5A by 84,3%, and the remaining 15,7% was influenced by other factors not examined in this study.